Pay attention, Carter Jones - Schmidt, Gary D. (Clarion Books, 2019)
One morning, Carter Jones answers the door to find a real English butler on the doorstep, one who once worked for Carter's grandfather. While Carter may not want to admit it, his family could use the help--his mother struggles to raise four children, his father is deployed to Germany and likely never coming back, and the whole family is struggling with his brother's untimely death. Not only does Carter learn proper decorum and the Queen's English from the butler, he also learns that the compassionate man can help heal his family.